HUBUNGAN KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA DI PUSKESMAS MASARAN 1 SRAGEN - Rismawati; Warsini (Jurnal Komunikasi Kesehatan, 2025)
The background to this research is that anemia is an iron deficiency that affects millions ofpeople throughout the world, especially pregnant women, which is caused by inadequate iron intake.Pregnant women are considered the group most at risk of developing anemia. The aim of this studywas to determine the relationship between adherence to consuming Fe tablets and the incidence ofanemia in pregnant women at the Masaran 1 Sragen Community Health Center. In this research, thetype of research used is quantitative research with a cross-sectional analytical research design. Thisresearch uses the sampling technique Accidental Sampling. The sample for this study was pregnantwomen in the third trimester at the Masaran 1 Sragen Community Health Center. The results of thisstudy show that there is a relationship between the compliance of pregnant women in consuming Fetablets and the incidence of anemia in pregnant women in the third trimester at the Masaran 1 SragenCommunity Health Center in 2024. Analysis using statistical tests using the Chi-square test found asignificant value of 0.000 < 0.05 so that Ha was accepted and Ho is rejected, it can be concludedthat there is a relationship between adherence to consuming Fe tablets and the incidence of anemiain pregnant women in the third trimester at the Masaran 1 Sragen Community Health Center.